Estimation in spot welding parameters using genetic algorithm - Lukman, Hafizi (2007)
Spot welding is an important metal joining process mainly in the automotive industries. Spot welding process needed parameters define by user such as current and time to finish one cycle of spot welding process. In this study, parameter of spot welding estimate using computer simulation. System identification is the field of modeling a system from experiment or simulation data. The application has widespread in many areas especially in system and control engineering. Genetic algorithm (GA) used as parameter estimation method for a model structure. By using Genetic algorithm (GA) the spot welding parameters can be estimated.